PENGARUH KUALITAS PRODUK, KUALITAS LAYANAN DAN CITRA MEREK TERHADAP KEPUASAN KONSUMEN (Studi Pada Waroeng Spesial Sambal “SS”, Cab. Sampangan) - Fitri Nur Rokhmat, 14.05.51.0115; Widyasari, suzy (Students' Journal of Economic and Management, 2019)
The purpose of this study is to analyze the effect of product quality, service quality, and brand image on customer satisfaction of Waroeng Spesial Sambal "SS", Cab. Sampangan city of Semarang. The population in this study were consumers who visiting Waroeng Spesial Sambal "SS" Cab. Sampangan city of Semarang. Sampling is done by "Purposive Sampling" technique, which is the of determining samples with certain considerations in accordance with the desired objectives. With the number of samples studied as many as 100 respondents. The collected data is then analyzed use factor analysis to test the validity of question items, Cronbach's alpha formula to test the reliability of the instrument, regression analysis to test the magnitude of the influence partially of each independent variable tested by the coefficient of determination and fit test models to test and prove the influence partially each independent variable. The results in this study show that product quality has a positive and significant effect on customer satisfaction, service quality does not affect consumer satisfaction, and brand image does not affect consumer satisfaction. The variable which has the greatest influence on customer satisfaction is product quality.